Evaluating the impact of biomaterials on modulating tumour-associated macrophages - Fareghdeli, Aroosha; Skillings, Robyn; Ahmed, Duale; Versey, Zoya; Cassol, Edana; Mostaço-Guidolin, Leila (CMBES Proceedings, 2024)
In recent years, biomaterials have been widely used for developing tumour models to help us gain a better understanding of tumour microenvironment (TME). Macrophages, as immune cells, play a significant role in the TME and exhibit plasticity based on their environment. This work aimed to assess the fundamental impact of biomaterials on the functionality of macrophages.